Methods of preventing and retarding the progression of myopia - Grudzińska, Ewa; Fabian-Danielewska, Anna; Gibka, Magdalena (Journal of Education, Health and Sport, 2019)
Myopia is an increasing problem worldwide. Its prevalence is predicted to over 4 billion of people in 2050, what would be almost 50% of the population. Therefore, authors have analyzed available literature in terms of treatment that may be able to prevent or slow the progression of myopia. There are risk factors such as genetic factors which nowadays could not be modified. However, there are other risk factor such as near work or protective factor such as time spent outdoor which could be modified. Moreover, therapeutic interventions seem to play more significant role. Among available methods it is mentioned: pharmacology including drops of atropine and pirenzepine, undercorrection, contact lenses, orthokeratology, bifocal or multifocal spectacles and soft multifocal contact lenses. Methods are described with their mechanism of action and efficacy.